A New Eurocode‐compliant Design Approach for Cold‐Formed Steel Sections. Issue 4 (14th September 2022) - Ungermann, Dieter; Lemański, Tim; Brune, Bettina
Abstract: A new, Eurocode‐compliant design approach based on the Direct Strength Method (DSM) combined with EN 1993‐1‐3 was developed for the design of thin‐walled cold‐formed steel sections. The new design approach transfers cross‐sectional resistance according to DSM, based on numerical elastic buckling analyses on the gross cross‐section, into the global stability check according to EN 1993‐1‐3. Experimental investigations on various perforated and unperforated cold‐formed sections in compression and bending serve to verify the new design approach. In addition, a numerical model was developed, it was calibrated on the test results and used for further parametric analyses on the load‐carrying capacity of cold‐formed sections.